MHD micropolar fluid flow with hall current over a permeable stretching sheet under the impact of Dufour-Soret and chemical reaction - Laltesh Kumar; Atar Singh; Vimal K Joshi; Kushal Sharma (International Journal of Thermofluids)
This research delves into the collective impacts of Hall-current, Soret-Dufour, magneto-hydrodynamics and Non-Darcy permeable medium on chemically reactive micropolar fluid flow over a stretching sheet. Employing advanced mathematical models and simulations, the study aims to elucidate these complex interactions. This study investigates micropolar fluid flow over a stretching sheet, accounting for the effects of melting and sliding. The subject is motivated by many industrial applications, such as metallurgical applications and polymer processing, where knowledge of fluid dynamics and heat transport is essential. The mathematical model includes the Navier-Stokes equations for micro-polar fluids and the Hall current effects with slip conditions. The problem is modelled based on the conservation of momentum with micropolar effects, energy, and species concentration. In addition, the energy calculation considers the melting effect on the stretching surfaces. The numerical solution to the problem is found by solving the partial differential equations using suitable techniques with the bvp4c tool in MATLAB. The investigation scrutinizes the impact of velocity slip, heat source, porosity, suction, volume fraction, chemical reaction, and viscous dissipation on velocity, heat transfer, and concentration profile. Results reveal notable influences, such as enhancements in velocity with increased porosity and nanoparticle volume fraction, while velocity slip and suction lead to velocity reduction. The findings offer valuable insights for optimising the efficiency of diverse technical applications.